Phylogenetic analysis and biological characteristics of an Akabane virus isolated in China - Li, Gan; Cai, Shikai; Liu, Xiyu; Li, Hairui; Qin, Limei; Zhao, Dengshuai; Huang, Junjie; Li, Ping; Zhang, Yuanhang; Zheng, Yajie; Zhang, Miaomiao; Gao, Han; et al. (Frontiers in Veterinary Science, 2025)
Akabane virus (AKAV) is an arbovirus that can cause miscarriage, premature birth, congenital malformations, and encephalomyelitis in young livestock. It is currently widely prevalent in China. Vero and MDBK cells were utilized to determine the virus titer and growth curve of the AKAV FS202301 strain in this study. Subsequently, the viral solution was intracranially (IC) or intraperitoneally (IP) inoculated into 8-day-old suckling mice, and the pathogenicity was explored by observing clinicopathological changes, and hematoxylin–eosin (HE) staining. Additionally, the S, M, and L segment sequences of the FS202301 strain were analyzed, phylogenetic trees were constructed, and antigenic epitopes were predicted to investigate its genetic variation. The results revealed that the viral titer of strain FS202301 was 106 TCID50/mL, with the number of viral copies peaking 24 h post-infection (hpi). This strain predominantly induced damage to the central nervous system, culminating in the death of suckling mice. It was classified as belonging to the genogroup Ia, exhibiting the highest degree of variation in the M segment, lower degrees of variation in the S and L segments, and no recombination events in any of the genes. The Gc protein encoded by the M segment contains more amino acid mutation sites and predicts a greater number of antigenic epitopes. This study aims to enhance the understanding of AKAV genetic variation in China and to establish a theoretical foundation for the future prevention and control of AKAV epidemics.